National Survey on the Impact of COVID-19 on the Mental Health of Australian Residential Aged Care Residents and Staff. Issue 1 (1st January 2022) - Brydon, Aida; Bhar, Sunil; Doyle, Colleen; Batchelor, Frances; Lovelock, Harry; Almond, Helen; Mitchell, Leander; Nedeljkovic, Maja; Savvas, Steven; Wuthrich, Viviana
ABSTRACT: Objectives: This study is the first to obtain data on the prevalence of, contributors to, and supports required for, pandemic-related distress within the residential aged care sector in Australia. A nested mixed-methods approach was used to examine aged care leaders' opinions about the impact of COVID-19 on the mental health of aged care residents and staff. Methods: A total of 288 senior staff of Australian residential aged care facilities (care managers, clinical care coordinators, and lifestyle team leaders; mean age = 52.7 years, SD  = 10.3) completed an online survey between 10 th September and 31 st October 2020. Results: On average, nearly half of their residents experienced loneliness (41%) and a third experienced anxiety in response to COVID-19 (33%). The most frequently noted contributors to poor mental health among residents were restrictions to recreational outings and watching news coverage relating to COVID-19. Participants emphasized the need for increased access to counseling services and improved mental health training amongst staff. Residential care staff were similarly impacted by the pandemic. More than a third of staff were reported as anxious (36%) and 20% depressed, in response to COVID-19. Staff were worried about introducing COVID-19 into their facility and were impacted by news coverage of COVID-19. Staff would feel supported by financial assistance and by increased staff-resident ratios. Conclusions: Senior staff perceive that the mental health of Australian aged care residents and staff was negatively impacted by the COVID-19 pandemic. The most noted contributors were identified, as was the mental health support for aged care communities. Clinical Implications: This study provides government and policymakers with clear intervention targets for supporting the sector. Clinicians can support residential aged care communities by providing on-site or telehealth counseling, and upskill and train residential aged care staff on how to respond to the emotional needs of residents in response to COVID-19.